Strategies to Prevent Increasing Divorce Rates for Muslim Families in Indonesia - Sururie, Ramdani Wahyu; Athoillah, Mohammad; Ulhaq, Muhammad Iqbal Zia (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The Annual Report of the Director General of Badilag from Religious Courts throughout Indonesia states that the number of divorces in Muslim families in Indonesia has increased over five years (2017-2021). The increasing number of divorces impacts childcare emotionally and physically because the average age of divorced couples is 20-40 years old who still have children in care, reaching 60%. This study aims to formulate a strategy to reduce the number of divorces in Indonesian Muslim families to create family resilience, especially for Muslim families. This study uses a qualitative approach with descriptive analysis. They collected data using questionnaires, document studies of religious court judges' decisions, interviews, and literature studies. By using the mashed sharia theory on the hifdu nasab aspect, this study finds that the strategy in reducing the number of divorce cases in Muslim families must be done holistically. The stages begin with the internalization of pre-marital education in the family from the institutionalization of pre-marital education in official institutions (KUA). Furthermore, husband and wife are given an understanding of methods for resolving marital conflicts and revitalizing the process of examining divorce cases in religious courts. Thus, this study concludes that what must be done to strengthen the resilience of Muslim families in Indonesia in reducing the number of divorces is to prevent it from upstream to downstream.